"Garage capitalism" as a form and process of post-socialist urban changes: Its pace, intensity and structural characteristics. A case study of Nis, Serbia. (August 2015) - Vasilevska, Ljiljana; Milanovic, Danijela; Nikolic, Marko; Vranic, Petar; Milojkovic, Aleksandar
Abstract: This paper considers the phenomenon known as "garage capitalism", accepted in literature as the transformation and adaptation of garages, residential space, basements and other space located on the ground floor of buildings into a space for retailing or other services, manifested at the beginning of the transition period in most Central East European countries. We analyzed this phenomenon as a spatial-functional form of two processes of post-socialist urban changes which significantly shaped the transformation of the urban fabric in post-socialist cities: 1) the increase in commercial functions, and 2) the restructuring of large housing estates from the socialist past. The research was conducted in the largest housing area built during socialism in the city of Nis, Serbia. The research focuses on: 1) the character of "garage capitalism", and the pace and intensity with which its proceeds – whether itis only a temporary occurrence from the turbulent early years of the transition period in the 1990s, or a solidified process over the past twenty-five years, and 2) scrutinizing its socio-spatial impact on the urban transformation of large housing estates. The analytical framework draws on empirical analysis and a questionnaire-based survey. The investigation indicates that despite a decrease in its intensity, "garage capitalism" is established as a solidified process of urban change. It also suggests that entrepreneurial attitudes and a laissez-faire approach to the urban planning of local authorities, under conditions of continuous economic recession, are the major drivers in the vitality of this process. Highlights: GC appeared in the early stage of post-socialist urban transformation. It signifies the transformation of the buildings ground floor into a retail space. It is spatial-functional product of important processes of post-socialist changes. GC established as a solidified process of urban changes in Serbia's cities. It reshapes existing urban patterns and urban forms of inherited neighborhoods.